TINDAK TUTUR DIREKTIF TOKOH UTAMA DALAM NOVEL “YANG TELAH LAMA PERGI” KARYA TERE LIYE (TINJAUAN PRAGMATIK) - Pembayun, Putri; Nitbani , Semuel H.; Djokaho, Margareta P.E. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
This research focus is based on the formulation of the problem and research objectives.This study aims to describe the form, function, and meaning of directive speech acts of the main character in the novel “Yang Telah Lama Pergi” by Tere Liye.Tere Liye's work. The theory used in this research is Pragmatics theory. Pragmatics is the study of the meaning of linguistic expressions in context. Pragmatics has a very close relationship with functional language use. Method method used in this research is descriptive qualitative because it is in accordance with the object and objectives that the researcher wants to achieve. The result of this research is in the form of directive speech acts used by the main character in Yang Telah Lama Pergi” by Tere Liye. The forms of directive speech acts in this study are 14 forms including 1) directive command 3 data, 2) directive request 5 data, 3) directive prohibition 1 data, 4) directive advice 1 data, 5) directive criticism 2 data, and 6) directive invitation 2 data, the most widely used form of speech acts is request speech acts. The functions of directive speech acts in this study are 14 forms including competitive function (competitive) 4 data, fun function (covivial) 2 data, collaborative function (collaborative) there are 6 data, conflictive function (conflictive) there are 2 data, the most widely used speech act function is the function of speech act function of working together (collaborative). Researchers hope that there will be further research analyzing the form, function and meaning of directive speech acts in novels.